The Effect of Blended Learning Model and Learning Motivation on Students’ Writing Ability of Public Islamic High School Students in Indonesia - Mayasari, Eka; Effendi, Mutiara Yulia (Regalia Institute, 2023)
The objective of the study is to investigates students’ writing ability of XII grade students in Public Islamic High School Tanjungpinang by comparing blended learning model and face-to-face learning model. This quasi-experimental study used two groups: the experimental group who were taught using blended learning and control group who were taught using face-to-face learning. The population was XII grade students. A sample of 60 students was divided into 2 groups, with 30 students as the control group and 30 students as the experimental group. The techniques for collecting the data were a test method by giving a written test and non-testing method by distributing a questionnaire. The results of study show that there is significant effect on students' writing ability and the learning model, there is significant effect on students' writing ability and learning motivation, and there is no interaction between learning models, learning motivation and writing ability.